INVESTIGATION OF SPEED CONTROLLED AND MINIMUM STATOR CURRENT OPERATION MODES OF ASYNCHRONOUS MOTORS (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, the integration of automated asynchronous electrical circuit block circuit devices and blocks into a single microprocessor system is highlighted, as well as increasing the functionality and speed of the electric circuit, it also leads to structural compactness.